93 SPERM PROTEIN 17 IS PREVALENTLY EXPRESSED IN HUMAN NERVOUS SYSTEM TUMORS IN FEMALE PATIENTS. (1st January 2006) - Grizzi, F.; Gaetani, P.; Franceschini, B.; Di Ieva, A.; Colombo, P.; Ceva-Grimaldi, G.; Rodriguez, R.; Baena, Y.; Dioguardi, N.; Frezza, E. E.; Cobos, E.; Chiriva-Internati, M.
Abstract : Purpose: Human sperm protein 17 (Sp17) is a highly conserved protein originally isolated from a rabbit epididymal sperm membrane and testis membrane pellet. Recently, Sp17 has been included in the cancer/testis (CT) antigens family and shown to be expressed in multiple myeloma and ovarian cancer. Here we investigate the immunolocalization of Sp17 in specimens of nervous system (NS) malignancies in order to establish the usefulness of this antigen as a target for tumor-vaccine strategies for NS tumors. Methods: The authors assessed the expression pattern of Sp17 in formalin-fixed and paraffin-embedded surgical specimens of NS malignancies, including 28 neuroectodermal primary tumors (6 astrocytomas, 16 glioblastomas multiforme, 5 oligodendrogliomas, and 1 ependymoma), 25 meningeal tumors, and 5 peripheral nerve sheath tumors (4 schwannoma, and 1 neurofibroma) using a standardized immunohistochemical procedure. Summary: A number of neuroectodermal (21%) and meningeal tumors (4%) were found heterogeneously immunopositive, and it was prevalently expressed in female patients (71%). No case among peripheral nerve sheath tumors was found to be immunopositive for Sp17. The expression pattern was found heterogeneous in all of the positive samples and it does not correlate with the degree of malignancy. Conclusions: The obtained frequency of expression and the heterogeneous cell distribution of Sp17 suggest the inability of this antigen to be used as a unique target for immunotherapeutic strategies in NS cancer. However, the present study firstly shows the immunolocalization of Sp17 in a proportion of cells of NS tumors but not in their normal counterpart. The emergent complex function of Sp17 renders necessary further studies to understand the link between immunopositive cells and this protein.